Faktor-Faktor yang Mempengaruhi Keberhasilan Pertumbuhan Tanaman Rehabilitasi Hutan dan Lahan Periode 2019-2024 Di DAS Saddang (Factors Influencing The Success of Plant Growth in Forest and Land Rehabilitation in the Saddang Watershed from 2019 to 2024) : - - Asikin Muchtar; Muh Bismar WWS; Wahyullah; Abd Kadir; Mahmud; Ummu Kultsum (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2025)
Forest and land rehabilitation is carried out annually to restore watershed conditions. In 2019, the BPDAS Jeneberang Saddang planted pine, candlenut, and sugar palm trees in Block 1 and 2, which cover ​​50 hectares each, in Rosoan Village, Enrekang District, Enrekang Regency, South Sulawesi Province. This study aims to determine the success rate and factors influencing the growth success of Forest and Land Rehabilitation (RHL) plant planted in 2019, and to determine the factors influencing their success. This study was a survei study. Data were collected through observations, interviews, and documentation. Data analysis were carried out using multiple linear regression with three independent variables: soil physical factors, soil chemistry, and socio-economic conditions. The results showed that the growth rate of pine (Pinus mercusii) was 36.36% (very low) or 432 trees/ha, candlenut (Aleurites moluccana) was 42.7% (very low) or 470 trees/ha, and sugar palm (Arenga pinnata) was 39.2% (very low) or 400 trees/ha. Soil physical factors such as clay texture (68.13%), and the solum depth of 20–25 cm have a significant effect on plant growth (F count 14.866 > 2.810; t count 3.856 > 1.679; sig. 0.000). Additionally, soil chemical factors (F count 7.940; sig. 0.007) and community socio-economic factors (F count 18.143; sig. 0.000) also showed a significant effect. This study recommended that BPDAS actively involve the surrounding community in intensive maintenance and budget for plant maintenance cost to optimize plant growth.